ASSESSMENT OF MANAGEMENT TRANSFER PROCESS OF WATER SUPPLY SYSTEMS IN SUNSARI DISTRICT OF NEPAL - Kumar Mishra, Anjay; Kumar Karna, Arun (International Journal of Research -GRANTHAALAYAH, 2019)
Considering water is most basic need and highest consumed goods for human being. The overall objective of the study is to identify the root causes of project performance deficiency and analyze the short comings of management transfer process of the system. The functional (Itahari) and partial functional (Duhabi) water supply and sanitation projects of Sunsari district of Nepal were selected for the study. Expert Consultation and Focus Group Discussion were done for primary source of data whereas reports. Journals, project reports, similar studies, books, websites and audit reports were reviewed for secondary source of data. Comparative performance of both the projects were analyzed based on technical, financial and institutional indicators along with the causes of project performance deficiency Worsening functionality, Worsening water quality and lost information were the weakness of water supply system lack of standard process, open defecation and financial issues were the main considerations to be taken by users committee to enhance their capacity for well-functioning of the system. For effective management Transfer of the system minimizing of these short comings, the system should be calibrated and should be sterilized. Project completion document should be handed over to WUSC. WUSC's WOS (Water Operators Standard) document and Business plan should be developed by WUSC in close consultation with the experts and trained WUSC about it. Access to and use of sanitary toilet by all in project area should be promoted. Ensuring these 6 indicators would be a good initiation towards the smooth management transfer.